2009
DOI: 10.1295/polymj.pj2009016
|View full text |Cite
|
Sign up to set email alerts
|

SiO2 Reinforcement and Morphology of a Novel Poly(imide-siloxane)-Based Thermal Plastic Elastomer Composite

Abstract: Silica (SiO 2 ) was used for the reinforcement of the poly(imide-siloxane) (PIS)-based thermal plastic elastomer. Trimethylsilyl modified SiO 2 was incorporated in the copolymer matrix to obtain the PIS/SiO 2 composties. In preparing the PIS/SiO 2 composite, the modified MeOH/THF solvent system provided a homogeneous reaction environment by offering good solubilities for the reactants and the intermediates while facilitating the dispersion of SiO 2 . The trimethylsilyl group modified fume silica offered excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ghosh et al indicated the polysiloxane grafted PIS had much higher T g of the polyimide hard block than PIS with the polysiloxane moiety in the main chain [22]. SiO 2 and TiO 2 were also used for the reinforcement of PISs, and the obtained composites had higher thermal stability than bare PISs [23,24]. In addition, crosslinking could increase the thermal stability of PISs at high temperature [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh et al indicated the polysiloxane grafted PIS had much higher T g of the polyimide hard block than PIS with the polysiloxane moiety in the main chain [22]. SiO 2 and TiO 2 were also used for the reinforcement of PISs, and the obtained composites had higher thermal stability than bare PISs [23,24]. In addition, crosslinking could increase the thermal stability of PISs at high temperature [25,26].…”
Section: Introductionmentioning
confidence: 99%